Student Worksheet Oriented on Assessment for Learning to Improve Learning Outcome on Acid Base Titration - Pratama, Danang Putra; Muchlis, Muchlis (Hydrogen: Jurnal Kependidikan Kimia, 2023)
This study aims to obtain student worksheet that can improve learning outcomes on acid-base titration material. The research method used in this research is the Research and Development (R&D) model of Borg and Gall with three steps, namely preliminary studies, development studies, and limited trials. The limited trials employed a one group pretest-posttest design. Data are derived from a validity score based on the mode, a practicality score derived from the student responses questionnaire results, and an effectiveness score derived from the results of the pretest, posttest 1, and posttest 2, which were analyzed by a parametric statistical test using the sample paired t-test. According to the study’s findings, the validity mode was obtained score â‰¥ 3 on each aspect, a practicality score of 98,14% and a significance of the t test obtained 0.000 in the first t-test and 0.000 in the second t-test, so that Student worksheet oriented on assessment for learning can be deemed feasible for raising student learning outcomes for the subject for acid-base titration. The presence of assessment for learning and feedback provided in student worksheet makes students active and can improve student learning outcome on acid base titration material.